The Problem of Typology of States and Legal Systems - Safaryan, Garnik; Malkhasyan, Liana (NAS RA)
The essence of the historical types of the state and law is one of the most important and crucial historical moments, without which it is not possible to correctly understand the development of their essence, their socio-political content and significance, their form, activity, or the change of their place and role in the political system of society.
Keywords: Legal Studies